PENYULUHAN PENGARUH KNEE JOINT PAIN EXERCISE PADA WARGA DENGAN KONDISI OSTEOARTHRITIS KNEE DI DESA GAMER KOTA PEKALONGAN - Irine Dwitasari Wulandari; Luvita Safitri (PENA ABDIMAS : Jurnal Pengabdian Masyarakat, 2022)
Geriatric is a term consisting of the words geros (elderly) and iatreia (caring / merumat), elderly if they have reached the age of over 60 years. Osteoarthritis, also called degenerative joint disease, is a disorder of the cartilage (joint cartilage) which is characterized by clinical, histological and radiological changes. From the observation process of identifying physiotherapy problems in the elderly by lecturers and D-III students of the Department of Physiotherapy, Faculty of Health, Pekalongan University, which was carried out by interviewing the elderly, it was found that the problem most often experienced by the elderly was joint pain in the knee. Situation analysis in the form of observations made by students in the environment of activities at RT.04 / RW.05 Gamer Village, Pekalongan Timur District, Pekalongan City in the form of interviews with the elderly. The process of observing the identification of physiotherapy problems in the elderly uses the assessment method. The purpose of this activity is to increase knowledge and understanding of the elderly about the role of physiotherapy in the elderly, especially in reducing joint pain, increasing muscle strength, and functional activities in osteoarthritis. The solution offered by students is to use counseling and training methods to reduce knee joint pain in the elderly with Knee Joint Pain Exercise intervention. The implementation of outreach and training activities was attended by four elderly people. Prior to the counseling and training process, the elderly were given a pre-test and post-test which were used as benchmarks for under-five understanding of the counseling and training carried out. The results of the pre-test and post-test proved that the level of understanding of the elderly increased after being given counseling and physiotherapy training. It can be concluded that after being given counseling and physiotherapy training, the level of understanding of the elderly in reducing knee joint pain in the elderly. Keywords: Osteoarthritis, and Knee Joint Pain Exercise